Shaping Graphic History: Primary Sources and Closure in Showdown! Making Modern Unions - Kristofferson, Rob; Orpana, Simon (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2018)
This research note examines the authors' graphic history Showdown! Making Modern Unions to build on recent scholarship about the pedagogical use of comics by considering the tools and possibilities this medium opens up to professional historians regarding the treatment of primary sources. We suggest that graphic histories enable strategies for using primary sources that actually enhance and popularize the ways historians can effectively use evidence, particularly in terms of building the critical consciousness of an expanded base of readers. Employing the comics theory concept of closure, we show graphic history to be uniquely situated to allow historians and readers to become actively engaged with and derive meaning from primary sources in a way not possible in other forms of historical writing. Examples from Showdown! are used to show the depth and breadth of these methodological possibilities.